Identifying predictors for bleeding in hospitalized cancer patients: A cohort study. Issue 158 (October 2017) - Patell, Rushad; Gutierrez, Alejandra; Rybicki, Lisa; Khorana, Alok A.
Abstract: Background: Bleeding and thrombosis are both major complications of hospitalization in cancer patients. Concern regarding bleeding risk may reduce compliance with thromboprophylaxis. We assessed incidence of major and clinically relevant non-major bleeding (MCRNMB) and identified risk factors associated with in-hospital bleeding risk in hospitalized cancer patients. Methods: We conducted a retrospective cohort study of consecutive adults admitted to general oncology floor at Cleveland Clinic from 11/2012–12/2014 ( n  = 3525). Patients were excluded for bleeding on admission ( n  = 108), age < 18 ( n  = 1), non-malignant disease ( n  = 2) and incomplete data ( n  = 56). Data collected included demographics, body mass index (BMI), cancer type, length of stay (LOS), use of anticoagulants and baseline laboratory values (+ 48 h). Univariate risk factors were identified with logistic regression analysis. Multivariable risk factors were identified with stepwise logistic regression and confirmed with bootstrap analysis. Results: The study population comprised 3358 patients of whom 69 (2.1%) developed MCRNMB. Median age was 62 (range, 19–98) years and 56% male. Median length of stay was 5 (range, 0–152) days. The majority of bleeding events were either gastrointestinal (GI) ( N  = 23, 33%) or retroperitoneal ( N  = 10, 14%). In multivariable analysis, anemia as the reason for admission (7.78, 95% CI 4.0–15.1, P  < 0.001), GI cancer site (2.96, 95% CI 1.7–5.2 P  < 0.001), BMI ≥ 40 (3.08, 95% CI 1.3–2.9, P  = 0.008) and thrombocytopenia (1.7, 95% CI 1.0–2.9, P  = 0.05) were predictive. Conclusion: The incidence of MCRNMB in a population of hospitalized cancer patients was 2.1%. Risk factors at admission included type of cancer and morbid obesity. Improved prediction of bleeding risk can assist physicians in optimizing selection of thromboprophylaxis in this population that is also at increased risk of VTE. Highlights: Bleeding concern may reduce thromboprophylaxis compliance in cancer inpatients. The incidence of bleeding in a population of cancer inpatients was 2.1%. Risk factors included cancer site, anemia, morbid obesity and thrombocytopenia. Improved prediction of bleeding risk can optimize selection of thromboprophylaxis.